Effect of Co-Driver on Job Content and Depression of Truck Drivers - Ali Hatami; Shahram Vosoughi; Agha F. Hosseini; Hossein Ebrahimi (Elsevier, 2019)
Background: Since the presence of a co-driver can be considered as a companion, partner, or friend for a driver through eliminating driver's loneliness, it plays a significant role in health and safety of drivers. The objective of this study was to investigate the effect of co-drivers on depression and occupational stress on male truck drivers. Methods: This study was an interventional case-control study. Seventy truck drivers were selected and divided into two groups: case (33 truck drivers with co-drivers) and control (37 truck drivers without co-drivers). Two Goldberg depression inventories (for evaluating driver's depression) and the Karasek job content questionnaire (for evaluating driver's job stress) were used to collect data which were completed by interview. Results: The results showed that job content values for the case group were higher in all dimensions except job nature. The comparison of the percentages showed significant difference between two groups. Depression rate in drivers with co-driver is truly less than depression rate in drivers without co-driver. There was significant positive relationship between dimensions of job content and depression rate. Conclusion: According to the results of this study, it can be claimed that a co-driver decreases stress and loneliness of drivers, as well as increases work performance and job satisfaction, and, in turn, leads to a decrease in job-related depression. Keywords: Co-driver, Depression, Job content, Job stress, Truck driver